Pengaruh Pengalaman Praktek Kerja Industri dan Motivasi Kerja Terhadap Kesiapan Kerja Siswa - Dina Indria Novita; Armida Armida (Universitas Negeri Padang, 2022)
This research was conducted to determine the effect of industrial work practice experience and work motivation on the work readiness of class XII students of office management automation at SMK Negeri 1 Solok. The type of data in this study is quantitative. A total of 118 students were used as the population. The data used is primary data. Data collection techniques using a questionnaire questionnaire. The sample technique used is proportional random sampling with 91 respondents as the sample. The method of analysis in this study is multiple linear regression using the SPSS V.21 application. To test the hypothesis, the research was carried out using data analysis through validity and reliability tests, normality tests, heteroscedasticity, multicollinearity, path analysis, F tests and statistical tests t at = 0.05. The results of this study indicate that 1) industrial work experience has a significant effect on work readiness 2) work motivation has a significant effect on work readiness 3) industrial work practice experience and work motivation have a significant effect on work readiness Keywords : industrial work practice experience, work motivation, work readiness